(untitled) (Journal of Parents and Teachers, 2014)
Games are a key element in the development of the person and at early age it is essential. There are different types of games through which the person communicates, understands, knows other cultures, etc. At school, these types of activities are fundamental due to the multitude of educational advantages and values they offer. They allow students to achieve some of the objectives that the teacher has previously set.